Alpha-synuclein shapes monocyte and macrophage cell biology and functions by bridging alterations of autophagy and inflammatory pathways - Limanaqi, Fiona; Zecchini, Silvia; Ogno, Pasquale; Artusa, Valentina; Fenizia, Claudio; Saulle, Irma; Vanetti, Claudia; Garziano, Micaela; Strizzi, Sergio; Trabattoni, Daria; Clerici, Mario; Biasin, Mara (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Abnormal spreading of alpha-synuclein (αS), a hallmark of Parkinson’s disease, is known to promote peripheral inflammation, which occurs in part via functional alterations in monocytes/macrophages. However, underlying intracellular mechanisms remain unclear. Methods: Herein we investigate the subcellular, molecular, and functional effects of excess αS in human THP-1 monocytic cell line, THP-1-derived macrophages, and at least preliminarily, in primary monocyte-derived macrophages (MDMs). In cells cultured w/wo recombinant αS (1 μM) for 4 h and 24 h, by Confocal microscopy, Western Blot, RT-qPCR, Elisa, and Flow Cytometry we assessed: i) αS internalization; ii) cytokine/chemokine expression/secretion, and C–C motif chemokine receptor 2 (CCR2) levels; iii) autophagy (LC3II/I, LAMP1/LysoTracker, p62, pS6/total S6); and iv) lipid droplets (LDs) accumulation, and cholesterol pathway gene expression. Transwell migration assay was employed to measure THP-1 cell migration/chemotaxis, while FITC-IgG-bead assay was used to analyze phagocytic capacity, and the fate of phagocytosed cargo in THP-1-derived macrophages. Results: Extracellular αS was internalized by THP-1 cells, THP-1-derived macrophages, and MDMs. In THP1 cells, αS induced a general pro-inflammatory profile and conditioned media from αS-exposed THP-1 cells potently attracted unstimulated cells. However, CCL2 secretion peaked at 4 h αS, consistent with early internalization of its receptor CCR2, while this was blunted at 24 h αS exposure, when CCR2 recycled back to the plasma membrane. Again, 4 h αS-exposed THP-1 cells showed increased spontaneous migration, while 24 h αS-exposed cells showed reduced chemotaxis. This occurred in the absence of cell toxicity and was associated with upregulation of autophagy/lysosomal markers, suggesting a pro-survival/tolerance mechanism against stress-related inflammation. Instead, in THP-1-derived macrophages, αS time-dependently potentiated the intracellular accumulation, and release of pro-inflammatory mediators. This was accompanied by mild toxicity, reduced autophagy-lysosomal markers, defective LDs formation, as well as impaired phagocytosis, and the appearance of stagnant lysosomes engulfed with phagocytosed cargo, suggesting a status of macrophage exhaustion reminiscent of hypophagia. Discussion: In summary, despite an apparently similar pro-inflammatory phenotype, monocytes and macrophages respond differently to intracellular αS accumulation in terms of cell survival, metabolism, and functions. Our results suggest that in periphery, αS exerts cell- and context-specific biological effects bridging alterations of autophagy, lipid dynamics, and inflammatory pathways.